Pemahaman guru terhadap pelaksanaan Pembelajaran sejarah Indonesia berdasarkan Kurikulum 2013 di SMKN 2 Bukittinggi - Desri Yulia; Ofianto Ofianto (Jurusan Sejarah FIS UNP, 2021)
Abstrak This study aims to find level of teacher understanding of the implementation of Indonesia history learning based on the 2013 curriculum which is carried out in Vocational High Schools (VHS) negeri 2 Bukittinggi. The study uses the mix method with quantitative and qualitative approaches. Collecting data are using assessment sheets, interview, observation, and documentation. The assessment sheet contains preliminary activities, core activities, scientific approach, and closing activities. The results showed that the level of understanding of Indonesian history teachers at SMKN 2 Bukittinggi on the implementation of 2013 curriculum learning was in the good category with a percentage rate of 78.7%. Based on indicators of preliminary activities 83.2%; Core activities 80.6%; scientific approach 69.8%; closing activities 81.3%. However, in planning the teacher did not make lesson plans based on the 2013 curriculum, in the rules the teacher did not understand the implementation of learning Indonesian history based on the 2013 curriculum, because in planning the lesson the teacher did not make lesson plans in accordance with the 2013 curriculum rules. Keyword: teacher understanding, learning, curriculum 2013